Predictors of Weight Loss Maintenance following an Insurance-Sponsored Weight Management Program. (11th March 2014) - Abildso, Christiaan G.; Schmid, Olivier; Byrd, Megan; Zizzi, Sam; Quartiroli, Alessandro; Fitzpatrick, Sean J.
Abstract : Intentional weight loss among overweight and obese adults (body mass index ≥ 25 kg/m 2 ) is associated with numerous health benefits, but weight loss maintenance (WLM) following participation in weight management programming has proven to be elusive. Many individuals attempting to lose weight join formal programs, especially women, but these programs vary widely in focus, as do postprogram weight regain results. We surveyed 2, 106 former participants in a community-based, insurance-sponsored weight management program in the United States to identify the pre, during, and post-intervention behavioral and psychosocial factors that lead to successful WLM. Of 835 survey respondents (39.6% response rate), 450 met criteria for inclusion in this study. Logistic regression analyses suggest that interventionists should assess and discuss weight loss and behavior change perceptions early in a program. However, in developing maintenance plans later in a program, attention should shift to behaviors, such as weekly weighing, limiting snacking in the evening, limiting portion sizes, and being physically active every day.